Предмет: Математика,
автор: Afk77
Спростити :
Ответы
Автор ответа:
0
√x-2√2 √x+2√2
√x-2√2
√x+2√2
------------- - ----------------- = ----------------- - -------------------- =
√(x²-4x√2+8) √(x²+4x√2+8) √(x-2√2)² √(x+2√2)²
√x-2√2 √x+2√2 √x-2√2
------------ - -------------- = -------------- -1
lx-2√2l x+2√2 lx-2√2l
При х<2√2 , lx-2√2l=-(x-2√2) и имеем:
√х-2√2
---------- =-1 и -1-1= -2
-(√х-2√)
lx-2√2l=x-2√2
x-2√2
--------- = 1 и 1-1=0
x-2√2
Ответ: -2 при х<0; 0,при х≥0.
------------- - ----------------- = ----------------- - -------------------- =
√(x²-4x√2+8) √(x²+4x√2+8) √(x-2√2)² √(x+2√2)²
√x-2√2 √x+2√2 √x-2√2
------------ - -------------- = -------------- -1
lx-2√2l x+2√2 lx-2√2l
При х<2√2 , lx-2√2l=-(x-2√2) и имеем:
√х-2√2
---------- =-1 и -1-1= -2
-(√х-2√)
lx-2√2l=x-2√2
x-2√2
--------- = 1 и 1-1=0
x-2√2
Ответ: -2 при х<0; 0,при х≥0.
Похожие вопросы
Предмет: Математика,
автор: Madikosh12008
Предмет: Литература,
автор: 1sassas1
Предмет: Химия,
автор: azizhasanov80
Предмет: Физика,
автор: Vеro4ka
Предмет: Обществознание,
автор: Arinapinina00